Business process management workshops : BPM 2014 International Workshops, Eindhoven, the Netherlands, September 7-8, 2014, Revised papers /: BPM 2014 International Workshops, Eindhoven, the Netherlands, September 7-8, 2014, Revised papers. (2015) - Unknown
No abstract available